USING OF THE CONDENSATION EFFECT AT HIGH-RHODIUM DUST SUPPRESSIO - O. V. Gerasimova (Литьë и металлургия, 2005)
Using of condensation process for gas treating from dust enabled not only to catch dust fine fractions and to reduce the expenses of gas treating as well.